Serum fibrinogen level and fibrinogen administration in patients with traumatic brain injury: A systematic review and meta-analysis protocol - Joanne Igoli; Jeremiah Oluwatomi Itodo Daniel; Halleluyah Oludele; Adedoyin Esther Alao; Idemudia Stephen Ogedegbe; Adewale Olaniyan; Michael Adeshola Adebayo; Damilola Matthew; Temidayo Elizabeth Oyepitan; Daniel Brabi; Olatomiwa Olukoya; Temidayo Osunronbi (PLoS ONE, 2025)
Introduction Traumatic Brain Injury (TBI) is a leading cause of disability and death globally. It has a significant economic burden. Coagulopathy has been identified as one of the key factors contributing to the poor outcomes observed in TBI patients, and it has been theorised that the management of coagulopathy will improve patient outcomes. Low serum fibrinogen levels denote a coagulopathic state, and the therapeutic administration of fibrinogen has been proposed to correct this state. However, there is no consensus on its efficacy in patients with TBI. Hence, this systematic review and meta-analysis seeks to ascertain the prognostic value of serum fibrinogen levels in patients with TBI and assess the effect of fibrinogen administration on these patients. Methods Using the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols (PRISMA-P) guidelines, we will perform a comprehensive search of Scopus, Medline, Embase and Cochrane Library to retrieve all original articles that investigate the prognostic value of fibrinogen levels and/or the effect of fibrinogen administration in TBI patients. Primary outcomes include functional outcome and mortality assessments such as the Glasgow Outcome Score and modified Rankin Score. Secondary outcomes include progressive intracranial haemorrhage/contusion and need for surgical intervention. Data collected will encompass participant demographics, measured fibrinogen levels, dose of fibrinogen administered and specified outcome measures. Conclusion Findings from this study, specifically the evidence if fibrinogen level has prognostic value and if fibrinogen administration improves patient outcomes, will help inform future TBI management. It will also enhance shared decision-making between healthcare professionals and patients if fibrinogen has a prognostic value, as this value could be used to communicate more effectively the expected prognosis post-TBI. Thus, TBI patient outcomes can be optimised accordingly. PROSPERO Registration Number CRD42024556497. Available from: https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42024556497